Simultaneous determination of anthocyanin and ponceau 4R in drink powders by derivative spectrophotometry and partial least-squares multivariate spectrophotometric calibration - Özgür, MÜ; Bozdogan, A; Erçag, A; Koyuncu, I (SPRINGER-VERLAG WIEN, 2001)
Two methods for the simultaneous determination of anthocyanin and ponceau 4R in drink powders by second derivative spectrophotometry and by partial least-squares multivariate spectrophotometric calibration are described. The procedures do not require any separation step. The methods were applied to determine both colorants in commercial gelatin powders; the results obtained are compared.
Keywords: derivative spectrophotometry; partial least-squares calibration; anthocyanin; ponceau 4R; food analysis; Chemistry